Peran Mediasi Learning Agility dalam Hubungan Perceived Community Support dengan Students Future Readiness - Fitriana, Nina; Fatimah, Malida (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The rapid advancement of technology, globalization, and the ever-changing dynamics of the job market require education to adapt and prepare the younger generation to face future challenges. Preparing students for the future is a central issue in 21st-century education, emphasizing not only academic achievement but also critical thinking, creativity, collaboration, communication, digital literacy, and character and leadership. However, various studies indicate that many students are not fully prepared for the real world after graduating from formal education. Mismatches between graduate competencies and workplace needs, poor problem-solving skills, limited technological skills, and a lack of awareness of social and environmental change are some indicators of students' low future preparedness. To successfully lead and manage learning in times of rapid change, leaders, educators, and students must think agilely—that is, be nimble, adaptive, flexible, and highly aware of their surroundings. One factor that can influence learning agility is community support. Therefore, the purpose of this study was to examine the mediating effect of learning agility on the relationship between community support and student future preparedness. This study used a quantitative approach with a survey method. The subjects in this study were 234 students obtained using convenience sampling. Data collection was conducted using the Perceived Community Support Scale, the Learning Agility Scale, and the Student Future Readiness Scale. Data analysis was performed using the Jamovi program. The analysis results indicated a partial mediating effect of learning agility on the relationship between perceived community support and student future readiness.